Comparison of the Reductions in LDL-C and Non-HDL-C Induced by the Red Yeast Rice Extract Xuezhikang Between Fasting and Non-fasting States in Patients With Coronary Heart Disease - Zhu, Li-Yuan; Wen, Xing-Yu; Xiang, Qun-Yan; Guo, Li-Ling; Xu, Jin; Zhao, Shui-Ping; Liu, Ling (Frontiers in Cardiovascular Medicine, 2021)
Background: Xuezhikang, an extract of red yeast rice, effectively lowers fasting blood lipid levels. However, the influence of Xuezhikang on the nonfasting levels of low-density lipoprotein cholesterol (LDL-C) and non-high-density lipoprotein cholesterol (non-HDL-C) has not been explored in Chinese patients with coronary heart disease (CHD). Methods: Fifty CHD patients were enrolled and randomly divided into two groups (n = 25 each) to receive 1200 mg/d of Xuezhikang or a placebo for six weeks as routine therapy. Blood lipids were repeatedly measured before and after six weeks of treatment at 0, 2, 4 and 6 hour (h) after a standard breakfast containing 800 kcal and 50 g of fat. Results: The serum LDL-C levels significantly decreased, from a fasting level of 3.88 mmol/L to nonfasting levels of 2.99, 2.83 and 3.23 mmol/L at 2, 4 and 6 h, respectively, after breakfast (P < 0.05). The serum non-HDL-C level mildly increased from a fasting level of 4.29 mmol/L to nonfasting levels of 4.32, 4.38 and 4.34 mmol/L at 2, 4 and 6 h postprandially, respectively, and the difference reached statistical significance only at 4 and 6 h after breakfast (P < 0.05). After six weeks of Xuezhikang treatment, the patients had significantly lower fasting and nonfasting serum levels of LDL-C and non-HDL-C (P < 0.05) than at pretreatment. The LDL-C levels were reduced by 27.8%, 28.1%, 26.2% and 25.3% at 0, 2, 4 and 6 h, respectively, and the non-HDL-C levels were reduced by 27.6%, 28.7%, 29.0% and 28.0% at 0, 2, 4 and 6 h, respectively, after breakfast. No significant difference was found in the percent reductions in the LDL-C and non-HDL-C levels among the four different time-points. Conclusions: Six weeks of Xuezhikang treatment significantly decreased LDL-C and non-HDL-C levels, with similar percent reductions in fasting and nonfasting states in CHD patients, indicating that the percent change in nonfasting LDL-C or non-HDL-C could replace that in the fasting state for evaluation the efficacy of cholesterol control in CHD patients who are unwilling or unable to fast.